2010
DOI: 10.1007/s00270-010-9922-y
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Laser Fiber Design on Outcome of Endovenous Ablation of Lower-Extremity Varicose Veins: Results from a Single Practice

Abstract: The design of laser fibers used for endovenous laser ablation (EVLA) in the management of lower-extremity varicose vein disease may affect treatment success. The purpose of this investigation is to report our experience using the gold-tip NeverTouch VenaCure laser fiber (AngioDynamics, Queensbury, NY) and to compare that to our experience with standard bare-tip fibers. A retrospective chart review of 363 consecutive EVLA treatments using the gold-tip laser fiber was performed. Demographic data including patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(13 citation statements)
references
References 7 publications
0
11
0
1
Order By: Relevance
“…22) The incidences of postoperative bruising and pain were significantly lower in the RF than in the BF group. In addition, the occlusion rate was 100% in the RF group, although LEED was significantly lower.…”
Section: Discussionmentioning
confidence: 91%
“…22) The incidences of postoperative bruising and pain were significantly lower in the RF than in the BF group. In addition, the occlusion rate was 100% in the RF group, although LEED was significantly lower.…”
Section: Discussionmentioning
confidence: 91%
“…5) Recently, the usefulness of a laser at a WSLW of 1470 nm has been emphasized. [6][7][8] Furthermore, various types of optical fiber, such as jackettip, 9) diffusion, 10) and radial 11) fibers, have been developed. Among these, radial fibers are optical fibers that reflect the laser beam by means of a prism, and the laser energy is emitted in a 360-degree manner, thus allowing homogeneous irradiation of the vein wall and making it possible to prevent perforation.…”
Section: Introductionmentioning
confidence: 99%
“…A radial fi bre with radial emission of laser light has been combined with a wavelength of 1,470 nm showing good results [14,40]. One study reported the results with a covered fi bre tip, which has a metal tube-case and a glass weld at the distal tip, showing slightly lower occlusion rates than a bare tip [15]. One of the most recent inventions is the tulip tip that is designed to prevent perforations by centring the laser fi bre within self-expandable blades [16,41] and the 2-ring-radial fi bre which proved to cause less pain during the fi rst two weeks after EVLA compared to the 980 nm-bare-fi bre combination [42].…”
Section: Parametersmentioning
confidence: 95%
“…Later on, technological advances led to radiofrequency segmental thermal ablation (RSTA) [13] and introduction of higher laser wavelengths as well as development of radial [14], covered laser fi bre tips [15] or tulip tipped catheters [16]. In addition, steam was used as an alternative heat source [17].…”
Section: Introductionmentioning
confidence: 99%